Tricarbonylbis(1,3-diisopropyl-4,5-dimethylimidazol-2-ylidene)iron - Ahmida, Aziza (International Union of Crystallography, 2012)
In the title compound, [Fe(C(11)H(20)N(2))(2)(CO)(3)], the Fe atom shows a distorted trigonal–bipyramidal geometry with three carbonyl and two carbene ligands. The latter have a cis arrangement, with a C—Fe—C angle of 90.60 (7)°. The Fe atom lies 0.007 (1) Å above the basal plane defined by two carbonyl and one carbene C atoms. The molecular structure is closely related to that of the isomolecular but not isotypic Ru complex with an identical cis arrangement, so, in general, bond geometries lie in expected ranges. In the crystal, C—H⋯O hydrogen bonds link the molecules into infinite zigzag chains extending along [010].